Valorisation of hybrid grouper bone gelatine: identifcation and in silico analysis of novel ace‑inhibitory and antioxidant peptides obtained via ultrafltration - Chan, Pei‑Teng; Patricia Matanjun; Chayo Budiman; Rossita Shapawi; Lee, Jau Shya (Springer Nature, 2025)
Purpose Bioactive peptides derived from fsh waste have attracted signifcant research interest in recent years because of their wide-ranging benefts, such as antioxidant, antihypertensive, and antimicrobial properties. This research aimed to generate dual-function peptides (ACE-inhibitory and antioxidant) from gelatine extracted from the bones of hybrid grouper via Alcalase hydrolysis. The antihypertensive and antioxidant efects are the most extensively investigated, with both exhibiting synergistic impact on cardiovascular health. Methods The Alcalase-treated bone gelatine hydrolysate was subjected to ultrafltration. The fractions were analysed for ACE-inhibitory and antioxidant activities. The peptide sequences of the potent fraction were identifed and subjected to in vitro gastrointestinal digestion. Results The Alcalase-treated bone gelatine hydrolysate demonstrated stronger ACE-inhibitory and antioxidant capacities than did the unhydrolysed bone gelatine. Fractionation of bone gelatine hydrolysate via ultrafltration yielded four fractions of varying molecular weights. The fraction containing peptides less than 1 kDa in size (ABGH-IV) presented the highest ACE-inhibitory and ferrous chelating activities (P<0.05), whereas the fraction with peptides greater than 5 kDa in size (ABGH-I) presented greater hydroxyl radical scavenging and reducing power (P<0.05). Notably, ABGH-IV demonstrated a greater ACE-inhibitory efect than PeptACE (an established commercial antihypertensive supplement). Seventy-fve novel ACE-inhibitory and antioxidant peptides were identifed in ABGH-IV, 11 of which were predicted to be highly active based on Peptide Ranker. These newly discovered peptides demonstrated stability against in vitro gastrointestinal digestion and resistance to ACE breakdown, suggesting their potential as natural ACE-inhibitor and antioxidants. Conclusion This study shows the potential of novel peptides isolated from hybrid grouper bone gelatine act against hypertension and oxidative stress.